Faktor-Faktor yang Berpengaruh pada Pemilihan Metode Kontrasepsi pada Pasangan Usia Subur (PUS) - Enita Nurjanah; Is Susiloningtyas (Journal of Medical Practice and Research, 2026)
The choice of contraceptive methods among couples of childbearing age is a key determinant of the success of family planning programs. Decisions regarding contraceptive use are influenced by multiple interrelated factors, including education level, knowledge, attitudes, communication between partners, access to and quality of health services, and support from health workers. Understanding these factors is essential for improving reproductive health outcomes. This study aimed to analyze the factors influencing contraceptive method selection among couples of childbearing age through a comprehensive literature review of national and international studies. Articles were identified from Google Scholar, PubMed, and Taylor & Francis databases based on relevance, accessibility, and recent publication. The review findings indicate that education level, partner communication, and health worker support are the most influential factors in contraceptive choice. Women with higher educational backgrounds tend to have better knowledge of contraceptive benefits and risks, leading to greater use of effective modern methods. Open and effective communication between partners increases agreement and readiness in selecting appropriate contraceptive methods. In addition, counseling, education, and guidance provided by health workers play a crucial role in improving awareness and appropriate contraceptive use. Social, economic, and cultural factors also indirectly influence contraceptive decision-making.